A Compact Ultra-Wideband Bandpass Filter with Sharp-Rejection using Complementary Split Ring Resonators - Mostafa Danaeian; Masoud Movahhedi; Ahmad Hakimi; Kambiz Afrooz (AUT Journal of Electrical Engineering)
A compact and sharp-rejection ultra-wideband (UWB) microstrip band-pass filter (BPF) is developed using of left handed metamaterials realized by complementary split ring resonator (CSRR). Moreover, proposed structure consists of two doublets parallel coupling gaps at each side of a microstrip ring. In comparison with some other filters, this structure shows a significantly wider passband due to the introduction of a cross-coupling between the feed lines (input and output) which generate four pairs of attenuation poles in the passband.On top of that, using two CSRRs etched in the back substrate side,and series gap inside the microstrip ring leads to the addition of two extra transmission poles at the lower and upper edges of the filter.Consequently, a compact six-pole ultra-wide bandpass filter is designed which exhibits extremely sharp rejection skirts around the target passband.The proposed filter has a passband covers3.4 to 10.15GHz andits measured 3dB fractional bandwidth is about 100%. Furthermore, rejection level better than 20 dB in upper stopband is extended to around 15.2 GHz both in simulation and measurement. Experimental verification is provided and good agreement has been found between simulation and measurement. To our knowledge, the size of proposed ultra-wideband filter is more compact in comparison with known similar filters.